Utilização dos serviços de saúde por mulheres em município com estratégia de saúde da família. - Carnevali, Bruna Feichas Renó (2016)
Introduction: The use of health services is a central element for the analysis of health systems and services. Women make up the majority of the Brazilian population, which in 2013 was equivalent to 51.4% of the population. They are also the main users of the Unified Health System (SUS) for their own care or monitoring of children and / or other relatives. Thus, they constitute a fundamental social segment for health policies. Objective: The objective of this study is to characterize the profile of women between 19 and 59 years of age who used health services. Method: population survey, in 2012, in the city of Praia Grande, State of São Paulo, which has a high coverage of the Family Health Strategy, in women aged 19 to 102 years. The independent variables included the sociodemographic characteristics, beneficiaries of the income transfer program, health plan users, service scheduling, medical exchange, health service exchange, health problems in daily activities, pap smear in the last 12 months, use of family doctor in the last 12 months, use of a gynecologist in the last 12 months, mammography in the last 12 months, clinical examination of the breasts in the consultations and contraceptive use. The dependent variables were: they attended health service and then performed papsmear, both in the last 12 months. For differences between proportions Pearson's Chi Square or Fisher's Exact, with significance level of 5% was used. Results: A total of 493 women were interviewed, with a average age of 39,63 years; The predominant socioeconomic class was C; Most did not have health insurance. Of the 65,31% (322) who attended the health service in the last 12 months, 64,70% scheduled their services easily and more than half would not change doctors or services; 64,77% of them considered their health good and more than 90% of them reported that the health condition does not interfere with their daily activities. Only 9% of the women were beneficiaries of income programs, with Bolsa Familia being the most used. The Pap smear exam was performed by 35,09% of the women interviewed in the last 12 months; More than 60% of them did not use the Family Health doctor in the last 12 months nor did they go through a Gynecologist. Mammography was performed in 24,23% and the breasts were examined in the consultations in 57,20%. Most did not use contraception. Conclusion: The profile found on the one hand expresses the conditionality of the use of health services foreseen in income transfer policies, and on the other, indicates that even in an area with high FHS coverage, affiliation to health plans still present sit self as an Important factor for access.